2023
DOI: 10.1037/apl0001114
|View full text |Cite
|
Sign up to set email alerts
|

When “who I am” is under threat: Measures of threat to identity value, meanings, and enactment.

Abstract: Although scholars across fields have studied threats to individuals' identities for their impact and ubiquity, the absence of standard scales has hindered the advancement of this research. Due to the lack of identity threat measures, the myriad existing propositions and models remain untested which may generate skepticism of the field. In the comparatively rare instances where deductive models have been tested, studies often suffer from methodological shortcomings related to the absence of a standard measure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 156 publications
(299 reference statements)
0
1
0
Order By: Relevance
“…However, while these extreme and unique cases are brought to unveil identity struggles, particularly across time (Kock, 2020; Pettica-Harris and McKenna, 2013), their design may limit the generalizability of the findings. Future research can extend the current study's contribution through the use of alternative methodologies, for example, quantitative longitudinal designs that incorporate measures such as the identity threat scale (see George et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, while these extreme and unique cases are brought to unveil identity struggles, particularly across time (Kock, 2020; Pettica-Harris and McKenna, 2013), their design may limit the generalizability of the findings. Future research can extend the current study's contribution through the use of alternative methodologies, for example, quantitative longitudinal designs that incorporate measures such as the identity threat scale (see George et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The source of the appraisal is undefined for identity threat, leaving open the potential for multiple triggers of threat, such as when only one identity is implicated. For example, George et al (2023) found that technological changes can threaten teachers' professional identities, and workplace discrimination can threaten employees' lesbian, gay, bisexual, transgender, queer or questioning identities. In these cases, individuals experience potential harm from sources other than additional identities they hold.…”
Section: Identity Threatmentioning
confidence: 99%